Implementation System Information Management Staffing Use Framesork Cobit 5 Domain Mea On Body Makassar State Civil Service - Alim Surya Saruman (Universitas Negeri Makassar, 2022)
The development of Information Technology (IT) has progressed rapidly. This development also affects the Information System (IS). Most organizations use and consider IS as an important part of business processes. The Makassar City State Civil Service Agency is a Civil Service Agency located in the Makassar City Government area that implements SI as a support for business processes. One of the SI used is the Personnel Management Information System (SIMPEG). SIMPEG is a system specifically designed to provide information on personnel administration management quickly, accurately, and functions to manage personnel data and information within the Makassar City Government work environment. The purpose of this study was to see the implementation of SIMPEG at BKN Makassar city. The results of this study indicated that the maturity level of the MEA01 and MEA02 processes reached 3.70 and 3.55 at level 4 which had been carried out within the limits set to achieve the expected results. And in the MEA02 process it reaches 3.36, namely at level 3, where this process has been carried out using certain predetermined processes, which are able to achieve the expected results. The recommendations given in general are expected to be used as input so that they can help improve the quality of IT governance in SIMPEG implementation